Developing an Integrated Framework for Managing Vocational Skill Programs for Deaf Students: A Case Study in an Inclusive Junior High School in Indonesia - Devira Putri Giana; Reza Akbar Fauzan (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2025)
This study investigates the management of vocational skill programs for deaf students within inclusive secondary education settings in Indonesia, specifically addressing the gap between national policy mandates and practical implementation at the school level. The research aims to develop an Integrated Inclusive Vocational Management (IIVM) framework, which is operationalized through a Four-Pillar model Universal Design for Learning (UDL), Assistive Technology (AT), Work-Based Learning (WBL), and Professional Development (PD), to enhance employability and social inclusion. Utilizing a qualitative case study approach, data were collected from SMPN 2 Tanggulangin, Sidoarjo, through in-depth semi-structured interviews, participant observations, and comprehensive document analysis. Findings reveal that while a robust legal framework exists in Indonesia, implementation is hindered by structural barriers, including a critical shortage of Special Advisor Teachers (GPK), physical infrastructure challenges exacerbated by environmental instability (chronic flooding), and a lack of standardized sign language instruction (SIBI vs. BISINDO). However, the school's "Program Belajar Unggul" and emphasis on digital literacy offer a viable pathway for vocational development if properly managed. The study proposes the IIVM management model, integrating UDL, inter-agency collaboration, and psychosocial support systems. It is recommended that vocational programs prioritize digital adaptability and soft skills to meet Industry 4.0 demands, transforming the educational environment from a medical model of deficit to a social model of accommodation